Implementasi Proses Pembelajaran Berbasis Profil Pelajar Pancasila Dalam Memperkuat Karakter Disiplin Peserta Didik: Studi Deskiptif di SMA Negeri 1 Pamarayan - Ronni Juwandi; Enday Nurmahdiyah; Holifah Holifah; Rosalia Fitriani; Tia Juliana; Titin Anggraeni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The aim of the research is to find out how to strengthen students' disciplined character in the school environment. This research was carried out at SMA Negeri 1 Pamarayan. The type of research in this research is descriptive qualitative, namely carrying out a learning process based on the Pancasila student profile to strengthen students' disciplinary character and the teacher strategies used to make it happen. The research sources are students and teachers, data collection techniques in this research are interviews, observation and documentation. Through the results of observations, researchers found that the implementation of the Project for Strengthening the Profile of Pancasila Students at SMA Negeri 1 Pamarayan produced results and had a very positive impact. Implementation of the Pancasila Student Profile Strengthening Project in schools, students' disciplinary character has developed. In the formation of disciplined character in students, several influencing factors were found, namely students, teachers, family and the social environment also played a role. Therefore, the project to strengthen the profile of Pancasila students needs to be implemented and instilled in students at school.